Physical and emotional abuse with internet addiction and anxiety as a mediator and physical activity as a moderator - Jinyin Peng; Yang Liu; Xubo Wang; Zhenxiu Yi; Lei Xu; Fulan Zhang (Scientific Reports)
Abstract This study aimed to explore the relationship between physical and emotional abuse (physical-emotional abuse) and Internet addiction in university students, as well as the mediating role of anxiety and the moderating role of physical activity. The data of physical-emotional abuse, anxiety and Internet addiction, and physical activity were measured by subjective questionnaire with convenience sampling in March 2024. A total of 1591 participants (806 males and 692 females) from Shanxi, Henan, Hunan and Hubei provinces in China were investigated. Subsequently, the relationships among the variables were explored using pearson correlation analysis. Finally, mediation and moderation models were assessed using the SPSS PROCESS macro plugin. After controlling for participants’ gender, grade level, and place of residence, only-child status, the study findings revealed that physical-emotional abuse significantly and positively predicted internet addiction and anxiety among university students (β = 0.157, β = 0.271, p < 0.001). However, upon the inclusion of anxiety as a variable, the predictive effect of physical-emotional abuse on internet addiction among university students became non-significant (β = 0.035, p > 0.05). Anxiety was found to have a significant complete mediating effect between physical-emotional abuse and internet addiction among university students. Additionally, physical activity significantly and negatively predicted anxiety (β = -0.062, p < 0.05), and the interaction term between physical-emotional abuse and physical activity also significantly and negatively predicted anxiety (β = − 0.053, p < 0.05). Physical activity moderated the first half of the mediation pathway from “physical-emotional abuse to anxiety to internet addiction.” Anxiety may be the internal mechanism of physical-emotional abuse affecting university students’ Internet addiction, and physical activity plays a moderator role in the relationship between physical-emotional abuse and university students’ Internet addiction. The study will provide new perspectives and strategies for the public health field to address physical-emotional abuse and Internet addiction among university students. It is also critical that future studies validate these findings on a large, multi-country basis.